2004
DOI: 10.1111/j.1440-1754.2004.00365.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of chronic lung disease in the ‘CPAP era’

Abstract: CLD remains prevalent in very low birthweight infants in the CPAP era. Oxygen requirement at 14 days is the strongest predictor of CLD. Infants requiring 30% oxygen or more while on CPAP at 14 days have a 60% risk of subsequent CLD or death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Indeed, a more recent comparison between two tertiary care neonatal centers suggested that, compared with conventional mechanical ventilation, the primary use of CPAP was associated with a lower incidence of bronchopulmonary dysplasia (65), a major cause of morbidity among neonatal intensive care survivors. Finally, current estimates suggest that CPAP is used in approximately one-half (and, especially in northern Europe, the majority) of preterm infants worldwide (18,28). Therefore, the compelling rationale for using CPAP is matched by strong evidence of its widespread use in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a more recent comparison between two tertiary care neonatal centers suggested that, compared with conventional mechanical ventilation, the primary use of CPAP was associated with a lower incidence of bronchopulmonary dysplasia (65), a major cause of morbidity among neonatal intensive care survivors. Finally, current estimates suggest that CPAP is used in approximately one-half (and, especially in northern Europe, the majority) of preterm infants worldwide (18,28). Therefore, the compelling rationale for using CPAP is matched by strong evidence of its widespread use in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Oxygen exposure is linked to the occurrence of BPD 3. Preterm human neonates have oxidant stress from birth, and animal data demonstrate poor antioxidant defences 4 5.…”
Section: Surviving Without Bronchopulmonary Dysplasiamentioning
confidence: 99%
“…Once extubated, apnoea/hypopnoea may limit the efficacy of NCPAP16 such that the lungs are not “opened up and kept open”,14 with atelectasis and desaturations increasing the Fi o 2 requirement. Given these limitations, early NCPAP use may not decrease BPD 3 41. For the VLBW infant at risk of BPD, the natural extension of NCPAP is NIPPV as it provides ventilatory support1820 22 and interacts with the neonate’s coordinated laryngeal and diaphragmatic muscle activities that control EEV 42…”
Section: Physiological Considerationsmentioning
confidence: 99%
“…The etiology of BPD is multifactorial and includes lung immaturity, oxygen toxicity, baro‐/volu‐trauma, and infections. Even in the surfactant era, it still occurs in newborns, who needed little or no ventilatory support and low oxygen concentration 3 . The lung histology of “new BPD” infants involves milder injury and fibroproliferation, but is associated with the disruption of alveolar and vascular growth.…”
mentioning
confidence: 99%